Breakfast Menu Development at Intercontinental Bandung Hotel Post Covid-19 - Bayu Nugroho; Rodolfo III S.M Caacbay (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
This study aims to analyze the development of the breakfast menu at the InterContinental Bandung hotel after covid - 19, this research was made using descriptive qualitative research methods, this research focuses on analyzing the differences in the development of the breakfast menu at the InterContinental Bandung hotel after and before covid - 19. The very obvious difference lies in terms of service which is more hygienic than before covid - 19. So that the new rules in the covid - 19 era make new policies that support people to live healthier and more hygienic lives. The results showed that the differences in the breakfast menu arrangement at the InterContinental hotel were very different before and after the arrival of covid - 19.